STEM in Croatia: Americanization of Education in Decline - Palijaš, Alen (International Journal of Research in STEM Education, 2024)
This paper critically examines the adaptation of American STEM educational practices within the Croatian education system, assessing their suitability and effectiveness given the significant socio-economic and demographic differences between the two countries. Through comparative analysis, the study juxtaposes the STEM education frameworks of the USA and Croatia, utilizing data from educational policy documents, student performance records, and demographic statistics to explore the transposition of educational models. The findings indicate that the direct transplantation of American STEM educational strategies into the Croatian context has not been entirely successful, due to Croatia's unique industrial landscape and ongoing population decline. The study highlights significant disparities in the effectiveness of STEM education, which are exacerbated by these national differences. The implications of this research are twofold. First, it suggests that countries need to consider their specific industrial and demographic contexts when adopting foreign educational models. Second, the study raises concerns about the sustainability of the Croatian education system's approach to preparing students for future STEM careers. The results call for a reevaluation of policy strategies, suggesting that more localized adaptations of STEM education may be necessary to address the unique challenges faced by countries like Croatia.